Analysis Of Vendor Income After The Traditional Market Revitalization Policy (Case Study: Simpang Market, Srimenanti, East Lampung Regency) - Ferdi Galang Bonanza; Emi Maimunah (International Journal of Economics, Business and Innovation Research, 2024)
This study investigates the differences in traders' income, number of customers, and retribution fees between before and after the market revitalization policy. Through a quantitative approach and data collection from relevant informants, followed by the Wilxocon signed rank test, the study found that the market revitalization policy led to a negative difference, namely a decrease in the income and number of consumers of market traders, as well as an increase in retribution costs after the market revitalization policy.